Videomodeling and Autonomy of People who have Autism. Review of Elements for an Educational Intervention Program - Martínez Rojas, Victoria Raquel (2024)
The application of video-modeling in an educational intervention program to develop the autonomy of students with autism spectrum disorder, level 3 severity (ASD3), is an element to take into account for the effective development of basic social skills, which are related to daily self-care routines (grooming and personal hygiene, food and clothing), as it is one of the main areas affected according to the clinical diagnostic criteria for autism spectrum disorder in the Diagnostic and Statistical Manual of Mental Disorders-5 (DSM-5) of the current American Psychiatryc Association. This article presents the particularities of the disorder and the guidelines to take into account for the application of this method in the process of designing an innovative educational intervention program aimed at Special Basic Education Centers considering technical, didactic and organizational aspects, as well as the proposals for educational inclusion in order to ensure the adaptation of the program both to the environment and to the peculiar diagnosis of the students. The methodology consists of a descriptive analysis based on the review of scientific production related to this type of disability and the application of the video-modeling method.